2021
DOI: 10.1108/jsocm-04-2021-0085
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Vaccinate against COVID-19: a Social Marketing perspective using the Theory of Planned Behaviour and Health Belief Model

Abstract: Purpose This study examines the factors influencing intention to vaccinate against COVID-19 in a developing country context using the theory of planned behaviour (TPB) and health belief model (HBM). Design/methodology/approach Through a cross-sectional survey design, the study adopted a quantitative approach to data collection and analysis. The study used an online survey to collect data from 478 respondents eligible to take the COVID-19 vaccine in Ghana. Findings Attitude, social norm, perceived behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 73 publications
(155 reference statements)
8
17
1
1
Order By: Relevance
“…The rate recorded in this study is much lower than the 83% reported in a similar study conducted in Ghana [52] prior to the initiation of vaccine administration in the country. However, much lower acceptance rates (51% and 54%) have been recorded in other studies conducted in Ghana among the general population [32,33].…”
Section: Plos Onecontrasting
confidence: 78%
See 2 more Smart Citations
“…The rate recorded in this study is much lower than the 83% reported in a similar study conducted in Ghana [52] prior to the initiation of vaccine administration in the country. However, much lower acceptance rates (51% and 54%) have been recorded in other studies conducted in Ghana among the general population [32,33].…”
Section: Plos Onecontrasting
confidence: 78%
“…Similar to the existing literature in Ghana [52], perceived severity did not significantly predict the decision to accept COVID-19 vaccines. This may be due to the low numbers of recorded deaths in the country compared with other countries and hence, people may have the tendency to think that even if they contract the virus they will recover.…”
Section: Plos Onesupporting
confidence: 74%
See 1 more Smart Citation
“…TPB is admittedly believed to be able to contribute and encourage a person's intention in getting vaccinated strongly (Twum et al, 2021). And attitude is one that is included in this theory (Chun et al, 2021, p. 3).…”
Section: Tables Figures and Formulasmentioning
confidence: 99%
“…Com base na TAP e no modelo de crenças em saúde, a pesquisa concluiu que 83% dos entrevistados estavam suscetíveis a tomar a vacina, e que os principais preditores da intenção foram as normas sociais e a facilidade ou dificuldade em tomar a vacina. O construto intenção sofreu variação significativa em pessoas de diferentes religiões (católica, muçulmana, outras religiões) e não apresentou variações signficativas quanto ao sexo e a idade (Twum;Ofori;Agyapong;& Yalley, 2021).…”
Section: Introductionunclassified